Combining stereotactic body radiotherapy with immunotherapy in stage IV non-small cell lung cancer - Liu, Xiaoli; Chi, Alexander (Frontiers in Oncology, 2023)
Immunotherapy has revolutionized the treatment of metastatic non-small cell lung cancer (NSCLC). Oligometastasis has been associated with better prognosis than widespread metastatic disease and may be curable by stereotactic body radiotherapy (SBRT). SBRT can stimulate immunogenic anti-tumor activity, which can be further augmented when combined with immunotherapy, such as immune checkpoint inhibitors (ICIs). Thus, its combination with immunotherapy was recognized as a promising treatment option, especially in the metastatic setting. However, the most optimal approach to combine SBRT with immunotherapy remains controversial with early clinical evidence emerging. Here, we review the current clinical evidence supporting the combination of SBRT with immunotherapy in the treatment of metastatic NSCLC. Also, we discuss the current controversies and areas for further exploration associated with this treatment strategy.